2012
DOI: 10.1152/ajplung.00116.2012
|View full text |Cite
|
Sign up to set email alerts
|

CFTR is required for maximal transepithelial liquid transport in pig alveolar epithelia

Abstract: A balance between alveolar liquid absorption and secretion is critical for maintaining optimal alveolar subphase liquid height and facilitating gas exchange in the alveolar space. However, the role of cystic fibrosis transmembrane regulator protein (CFTR) in this homeostatic process has remained elusive. Using a newly developed porcine model of cystic fibrosis, in which CFTR is absent, we investigated ion transport properties and alveolar liquid transport in isolated type II alveolar epithelial cells (T2AECs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 40 publications
4
52
0
Order By: Relevance
“…Another study reported that increased functional CFTR decreases ENaC activity by raising intracellular Cl 2 (47). However, studies in newborn pigs with CF disease found no evidence for increased Na 1 reabsorption across airway epithelia (48,49). Herein we report that ΔF508 mice have significantly more negative amiloride-sensitive NPD values (223 vs. 27 mV for wild-type mice), which is in agreement with previous reports in mice (50) and humans with CF (51).…”
Section: Discussionsupporting
confidence: 92%
“…Another study reported that increased functional CFTR decreases ENaC activity by raising intracellular Cl 2 (47). However, studies in newborn pigs with CF disease found no evidence for increased Na 1 reabsorption across airway epithelia (48,49). Herein we report that ΔF508 mice have significantly more negative amiloride-sensitive NPD values (223 vs. 27 mV for wild-type mice), which is in agreement with previous reports in mice (50) and humans with CF (51).…”
Section: Discussionsupporting
confidence: 92%
“…(Bove et al, 2010) Adult porcine CFTR-mediated transepithelial liquid transport. (Li et al, 2012) ECM, extracellular matrix; KGF, keratinocyte growth factor; SPA, SPB, SPD, surfactant proteins A, B, and D.…”
Section: Species/age Notes On Protocols and Results Referencesmentioning
confidence: 99%
“…Using isolated type II alveolar epithelial cells and ex vivo studies of newborn lungs, their data indicated that CFTR was not required for basal liquid absorption but was required for cAMP-stimulated liquid absorption and secretion, suggesting that the apical liquid layer is controlled by a number of ion channels at both the apical and basolateral membranes (47). These results are consistent with previous results of Matthay and coworkers (19,25), who suggested that CFTR is important for apical-basolateral fluid transport in cultured human alveolar epithelial type II cells.…”
Section: Mucus and Fluid Transportmentioning
confidence: 99%